Factor Theorem

The Factor Theorem says that
If a function/expression becomes zero at a value 'c' then `x - c` is a factor of that function/expression.
For example, `x^2 - 3x + 2` becomes zero at x = 2:
`(2)^2 - 3*(2) + 2 = 4 - 6 + 2 = 0`
Thus, by factor theorem, `x - 2` is a factor of the expression `x^2 - 3x + 2`. Another value at which this expression becomes zero is x = 1. Thus `x - 1` is also a factor of the expression. Thus, we can write
`x^2 - 3x + 2 = (x - 1)(x - 2)`

No comments:

Post a Comment

Search This Blog